Analysis of scientific argumentation skills of prospective biology teacher students in inquiry-oriented laboratory activities - Cahyani, Dewi; Gloria, Ria Yulia; Roviati, Evi (Universitas Negeri Jakarta, 2024)
Laboratory activities are essential and meaningful in science learning, especially biology. However, students often have no sufficient understanding of what is being practiced, beside they do not use their sklills to solve problems in the field of biology. Scientific argumentation is one of the skills that a prospective science teacher needs to develop and needs to be trained so that prospective teachers have experience and skills to apply when they become teachers later. The scientific argumentation skills in laboratory activities needs to be trained to provide training to students to use the results of laboratory activity to answer problems in the field of biology. This study aims to apply inquiry-oriented laboratory activities that focus on scientific argumentation in laboratory courses and to analyze the quality of scientific arguments of prospective biology teacher students during laboratory activities. The method used in this study is mixed methods research type exploratoryy which combines qualitative and quantitative approaches with complementarity. The research subject is a prospective student of a 5th semester biology teacher who takes microbiology courses. The results showed that the application of scientific argumentation in laboratory activity was carried out in 3 stages, namely initial discussion, experiment, observation and final discussion after experiment. The results of the analysis of the quality of scientific argumentation show that the argumentation skills of some students is at the middle level. The conclusion of this laboratory activity shows that students' scientific argumentation skills can develop well if they have the opportunity to discuss critically by using experimental data and their knowledge obtained from literature studies.